Improving Patient Outcomes in mTBI: The Role of Integrated Nursing Interventions in the Emergency Department - Feng T; Zhao P; Wang J; Du X; Ai M; Yang J; Li J (Therapeutics and Clinical Risk Management)
Ting Feng, Peng Zhao, Jiao Wang, Xiaoye Du, Meimei Ai, Jing Yang, Junjie Li Department of Emergency, Xijing Hospital, Air Force Medical University, Xi’an, Shaanxi, 710032, People’s Republic of ChinaCorrespondence: Ting Feng, Department of Emergency, Xijing Hospital, Air Force Medical University, Xi’an, Shaanxi, 710032, People’s Republic of China, Email fengtingff24@163.comBackground: Traumatic brain injury (TBI) is a major cause of morbidity and mortality, often requiring emergency department (ED) management. Integrated Nursing Interventions play a critical role in the care of TBI patients, but limited research has evaluated their efficacy in this setting. This study aims to assess the impact of Integrated Nursing Interventions on patient outcomes and complications in the ED.Methods: This retrospective study included 246 patients with mild traumatic brain injury (mTBI) treated in the emergency department from January 2022 to December 2022. Of these, 138 patients received Integrated Nursing Interventions, while 108 did not. Baseline characteristics, clinical outcomes, and complications were compared between the two groups. Descriptive statistics, logistic regression, and receiver operating characteristic (ROC) curve analysis were used to evaluate the effect of nursing interventions on outcomes such as mortality, complications, and hospital stay.Results: Among the 246 mTBI patients, those receiving Integrated Nursing Interventions (n=138, 56.1%) experienced significantly lower rates of adverse events, including perioperative intracranial hemorrhage (4.3% vs 12.0%, P=0.025) and shorter hospital stays (6± 2 days vs 11± 3 days, P< 0.001). The study sample included 56.5% female, with 80.1% age ≤ 80. Integrated Nursing Interventions refer to coordinated care strategies that combine multiple nursing approaches tailored to address both physical and psychological needs of patients. For instance, the use of patient education combined with individualized pain management strategies. Logistic regression analysis revealed that Integrated Nursing Interventions were associated with a significant reduction in in-hospital mortality (OR=1.828, 95% CI: 1.619– 2.318, P< 0.001). ROC curve analysis demonstrated strong predictive accuracy for outcomes such as readmission rate (AUC=0.757), 30-day mortality (AUC=0.836), and 90-day mortality (AUC=0.760).Conclusion: Integrated Nursing Interventions in the emergency department significantly improve patient outcomes for mTBI patients, reducing mortality, complications, and length of hospital stay. These interventions, which include early assessment, timely intervention, patient education, and collaborative care, are essential for optimizing TBI management. The high predictive value of these interventions further underscores their importance in emergency care. Future research should focus on the long-term effects of Integrated Nursing Interventions on patient outcomes across different age groups, particularly in chronic disease management. Further studies could explore the role of digital health tools in enhancing integrated care.Keywords: traumatic brain injury, emergency department, nursing interventions, prognosis, patient management